`Residual bodies' in sarcoid and sarcoid-like granulomas - Williams, W. Jones (1967)
A morphological and histochemical study was made of epithelioid cell granulomas: (a) classical sarcoid type, namely, sarcoidosis, Kveim tests, tuberculosis, farmer's lung, and Crohn's syndrome; (b) sarcoid-like granulomas, often distinguishable from (a) by the presence of extracellular mucin or bile, namely, ulcerative colitis, diverticulitis, cholecystitis, cholangitis, carcinoma of the rectum and lymph nodes, draining tumours. All these granulomas showed similar, numerous cytoplasmic granules in epithelioid and giant cells with the properties of residual bodies, i.e., end products of activated lysosomes. The presence of residual bodies demonstrates the following features the morphological similarity of the granulomas studied, and the phagocytic nature of the affected cells. It suggests a common mechanism of granuloma formation but does not identify any particular exogenous cause. The findings suggest that Boeck's sarcoidosis may be caused by unidentified exogenous agents.